Jurisprudential Principles of Article 23 of the Family Protection Law - Mohammad Imam; Seyed Ali Razavi; Seyed Mohammad Razavi (آموزه‌‌های فقه مدني, 2020)
According to Article 23 of the Family Protection Law of 2012 (1391 in the Solar Hijri calendar), couples must provide the necessary certificates for infectious and dangerous diseases before marriage while undergoing medical tests. In the jurisprudence of Islamic religions, there is a difference of opinion among jurists regarding the jurisprudential ruling of such experiments. Some hold to the reasons such as the traditions narrated from Imams, the rule of prohibition of detriment, the necessity of obedience to the laws of the Islamic government, logical and consistent usages (usages of the wise) and so on. On the other hand, others by rejecting the above view and holding to the prohibition of the marriage contract and the conditions for its validity, and some narrations have preferred the non-obligatory of it. Based on the findings of the present article, which is done in an analytical-descriptive manner, it can be concluded that although due to lack of explicit text, the necessity of such experiments cannot be accepted as the primary rule and if there is a need for dangerous diseases such as AIDS and… which causes the infection and destruction of the person and the health of the people of the society, performing these tests in suspicious cases, in order to observe social interests, is obligatory due to the secondary rule, but in other cases, although testing is preferable, but not legally obligatory.